2017
DOI: 10.1111/tct.12714
|View full text |Cite
|
Sign up to set email alerts
|

Role of pelvic ultrasound simulation

Abstract: All 28 respondents believe that ultrasound simulation is a useful complement to learning with real patients, with the potential to improve their pelvic ultrasound performance, interpretation skills and clinical reasoning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 10 publications
0
9
0
4
Order By: Relevance
“…Az ultrahang-diagnosztika a nőgyógyászatban is jelentős szereppel bír [2]. Ez a modalitás a leggyakoribb és általában az elsőként választandó módszer a méh megítélésére.…”
Section: Az Ultrahangvizsgálat Szerepe a Nőgyógyászatbanunclassified
See 1 more Smart Citation
“…Az ultrahang-diagnosztika a nőgyógyászatban is jelentős szereppel bír [2]. Ez a modalitás a leggyakoribb és általában az elsőként választandó módszer a méh megítélésére.…”
Section: Az Ultrahangvizsgálat Szerepe a Nőgyógyászatbanunclassified
“…A transvaginalis ultrahang (TVS) könnyen elérhető, költséghatékony és nem invazív, ezért az első diagnosztikai eljárásként alkalmazható megnagyobbodott méh, alhasi fájdalom és vérzészavar esetén [3][4][5][6]. TVS-vizsgálat során megfelelő képet kaphatunk az endometriumról, a myometriumról és elváltozásaikról is -mint például myoma, polyp, adenomyosis -, ennélfogva a méh diagnosztikájában kiemelkedő fontosságúvá vált [1,2]. Számos tanulmány foglalkozott már a nőgyógyászati ultrahangvizsgálatok érzékenységének, specifici-tásának összehasonlításával, más modalitásokkal, úgymint hiszteroszkópia, illetve MR, melyekben meggyőző eredményeket közöltek, így nem meglepő, hogy az ultrahangvizsgálat a mindennapi rutin nőgyógyászati diagnosztika kiemelt, elsődleges résztvevője [7].…”
Section: Az Ultrahangvizsgálat Szerepe a Nőgyógyászatbanunclassified
“…More recently, a virtual reality pelvic US simulation workshop using a new generation of simulation techno logy (VIMEDIX, CAE Health care, Sarasota, USA, and Ville St. Laurent, Quebec, CAN, and Simbionix US mentor, 3D Systems Health care, Littleton, CO, USA) was conducted at our simulation center. 15 Pelvic US simulation activity lasted 4 hours and consisted of three modules: abnormal uterine bleeding, adnexal masses, and bleeding in pregnancy. All learners completed a pre-and postencounter quiz, and an anonymous postsimulation survey on relevance of US simulation to clinical learning and its usefulness to improve scanning performance and interpretation skills.…”
Section: How To Adapt Simulation For Donald School Needs?mentioning
confidence: 99%
“…Postworkshop survey indicated that US simulation is a useful complement to learning on real patients that has a potential to improve their pelvic US performance, interpretation skills, and clinical reasoning. 15…”
Section: How To Adapt Simulation For Donald School Needs?mentioning
confidence: 99%
“…Of the publications to date that studied trainee's perspectives of TVUS simulation training, most are quantitative studies using questionnaires or self-assessed confidence scores [10,[13][14][15][16][17] with one mixed methods study [12]. In contrast, qualitative research allows use of open-ended questions that aim to explore what is important to the trainee themselves.…”
Section: Introductionmentioning
confidence: 99%